The Survei Minat Masyarakat Desa Kuripan Untuk Melanjutkan Pendidikan - Suanto Suanto; Alinurdin Alinurdin; Setiawati Setiawati; Nurdiyana Nurdiyana (Jurnal Indragiri Penelitian Multidisiplin, 2022)
There are still some educational problems, one of which is the level of public education which is still quite low in some areas, one of which is Kuripan village where the education index has only reached 65% (Human Development Index (HDI) in 2019). This is certainly a concern of the village government in order to increase the public education index which of course ultimately focuses on the development of human resources and the community's economy. This study aims to analyze data empirically about the interest of the Kuripan village community to continue their education. where the respondents who are used as data sources are the village community. This study uses a survey method. The results showed that the public's interest in continuing education was quite high, as seen from the analysis of the survey results which showed that 96% of children had aspirations to go to school to a higher level. This data is supported by survey results which state that all parents strive so that their children can continue to a higher level of education. Parents also already have a mindset that education is considered important, this can be seen based on the results of a survey which shows that 94% of parents state that school is important. Of course the survey results are very good for increasing the level of children's education because the mindset of the village community, especially parents, about the importance of education is very open. Constraints faced are economic factors, where 60% of parents stated that economic factors were an obstacle to continuing their children's schooling to a higher level. And another factor is school facilities, there is only 1 high school level in the Kuripan village areas